Citation et autocitation dans la peinture de Greco - Guillaume Kientz (Civilisations et Littératures d’Espagne et d’Amérique du Moyen Âge aux Lumières (CLEA) - Paris Sorbonne, 2021)
Starting from the very project of the great Greco retrospective (Grand Palais, Paris), the main topic here is to evoke, in a diachronic way, the unique course of Greco, in order to highlight his singular initiatory path of formation which led him to invent his palimpsest painting in which the moderns and the avant-garde recognized themselves. This article is organized into three stages: tradition and innovation; invention and variations; borrowing and reformulations. Drawing on numerous examples, the subject demonstrates the coherence and evolution of Greco's painting from one of its fundamental characteristics: the serial process.